Micro-Opto-Electro-Mechanical Systems for High-Precision Displacement Sensing: A Review - Chenguang Xin; Yingkun Xu; Zhongyao Zhang; Mengwei Li (Micromachines, 2024)
High-precision displacement sensing has been widely used across both scientific research and industrial applications. The recent interests in developing micro-opto-electro-mechanical systems (MOEMS) have given rise to an excellent platform for miniaturized displacement sensors. Advancement in this field during past years is now yielding integrated high-precision sensors which show great potential in applications ranging from photoacoustic spectroscopy to high-precision positioning and automation. In this review, we briefly summarize different techniques for high-precision displacement sensing based on MOEMS and discuss the challenges for future improvement.